Implementasi Kebijakan Angela Merkel Terhadap Gelombang Pengungsi Timur Tengah - Steffy (Jurnal Alternatif - Jurnal Ilmu Hubungan Internasional, 2023)
This study aims to analyze the implementation of Angela Markel's policy towards the Middle East refugee wave through the CEAS policy and the Open Door Policy that was implemented, in response to the refugee crisis in Europe in 2015. This is a problem because of the many different perceptions of refugees coming from the Middle East and because Germany is the leader of the European Union in enforcing its members to implement these policies. This study uses a qualitative method with a descriptive analysis approach using secondary data. At the national or domestic level, this policy has drawn many protests and criticisms from the public, opposition parties, and Merkel's own party, interest groups and the European Union regarding this policy. Despite receiving many rejections, Merkel remains adamant and continues to implement the policy in Germany, this is because Merkel has a point of view or perception about refugees who must be assisted in seeking protection and security. This study uses the theory of Angela Merkel's Foreign Policy and the Theory of the Copenhagen School in examining the policies issued by Merkel regarding Middle Eastern refugees.